The Role of School Principals in Improving Education Quality Management in State Elementary School 149/IV Jambi City - Putri, Nadella; Munandar, Aris; Jordiansyah, Muhammad; Noviasari, Yuli; Karmila, Karmila; Nazilah, Hikmatun; Wati, Herna; Paridotullah, M. Adi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The role of the principal has a significant impact on improving the quality management of education in schools. The quality of education reflects the effectiveness of the educational system in providing knowledge, skills, and values to students through effective teaching methods and adequate facilities. This study aims to explore the role and efforts of the principal of SDN 149/IV Kota Jambi in managing education quality. The principal's roles include: 1) optimizing teacher professional development through curriculum activities, 2) encouraging student achievements, 3) building relationships with school committees, parents, and the community, and 4) providing school facilities and infrastructure. This study employs a qualitative descriptive method, with data collected through observation, interviews, and documentation. Data analysis is conducted using source triangulation to test credibility. As the primary manager of the school, the principal holds a strategic role in ensuring excellent education quality at SDN 149/IV Kota Jambi, making it a competitive school across various fields.